Assessment of the optimal number of positive biopsy cores to discriminate between cancer-specific mortality in high-risk versus very high-risk prostate cancer patients - Wenzel, Mike; Würnschimmel, Christoph; Chierigo, Francesco; Tian, Zhe; Shariat, Shahrokh F; Terrone, Carlo; Saad, Fred; Tilki, Derya; Graefen, Markus; Roos, Frederik C; A Kluth, Luis; Mandel, Philipp; et al. (The Prostate, 2021)
BACKGROUND: Number of positive prostate biopsy cores represents a key determinant between high versus very high-risk prostate cancer (PCa). We performed a critical appraisal of the association between the number of positive prostate biopsy cores and CSM in high versus very high-risk PCa. METHODS: Within Surveillance, Epidemiology, and End Results database (2010-2016), 13,836 high versus 20,359 very high-risk PCa patients were identified. Discrimination according to 11 different positive prostate biopsy core cut-offs (≥2-≥12) were tested in Kaplan-Meier, cumulative incidence, and multivariable Cox and competing risks regression models. RESULTS: Among 11 tested positive prostate biopsy core cut-offs, more than or equal to 8 (high-risk vs. very high-risk: n = 18,986 vs. n = 15,209, median prostate-specific antigen [PSA]: 10.6 vs. 16.8 ng/ml, <.001) yielded optimal discrimination and was closely followed by the established more than or equal to 5 cut-off (high-risk vs. very high-risk: n = 13,836 vs. n = 20,359, median PSA: 16.5 vs. 11.1 ng/ml, p < .001). Stratification according to more than or equal to 8 positive prostate biopsy cores resulted in CSM rates of 4.1 versus 14.2% (delta: 10.1%, multivariable hazard ratio: 2.2, p < .001) and stratification according to more than or equal to 5 positive prostate biopsy cores with CSM rates of 3.7 versus 11.9% (delta: 8.2%, multivariable hazard ratio: 2.0, p < .001) in respectively high versus very high-risk PCa. CONCLUSIONS: The more than or equal to 8 positive prostate biopsy cores cutoff yielded optimal results. It was very closely followed by more than or equal to 5 positive prostate biopsy cores. In consequence, virtually the same endorsement may be made for either cutoff. However, more than or equal to 5 positive prostate biopsy cores cutoff, based on its existing wide implementation, might represent the optimal choice.
Keywords: Prostatic Neoplasms; Adenocarcinoma; prostata; nádory prostaty; program SEER; Humans; biopsie dutou jehlou; lidé středního věku; Aged; senioři; lidé; Prostatectomy; Neoplasm Grading; Male; Prostate; Middle Aged; Retrospective Studies; stupeň nádoru; adenokarcinom; retrospektivní studie; prostatektomie; Risk Assessment; SEER Program; míra přežití; mužské pohlaví; hodnocení rizik; Biopsy, Large-Core Needle; Survival Rate